Situating Public Intellectuals. Issue 1 (August 2015) - Marshall, P. David; Atherton, Cassandra
The concept of the public intellectual has always been a somewhat contested term. This article serves as both an introduction to the debates around what it constitutes and an entry point into how the new media environment is producing a different configuration of the public intellectual. Through key thinkers who have addressed the idea of the public intellectual internationally and those who have focused on the Australian context, this essay positions the arguments made by the authors in this special issue. Via a short case-study of TED, the conference and online idea-spreading phenomenon, it argues that the contemporary moment is producing and privileging a different constellation of experts as celebrities that match the exigencies of online attention economy. A shifted conception of the public intellectual is beginning to take shape that is differently constituted, used and situated, and this article helps to define the parameters for further discussion of these transformations.